2015
DOI: 10.1016/j.psyneuen.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal distress associates with placental genes regulating fetal glucocorticoid exposure and IGF2: Role of obesity and sex

Abstract: Maternal emotional distress symptoms, including life satisfaction, anxiety and depressed mood, are worse in Severely Obese (SO) than lean pregnancy and may alter placental genes regulating fetal glucocorticoid exposure and placental growth. We hypothesised that the associations between increased maternal distress symptoms and changes in placental gene expression including IGF2 and genes regulating fetal glucocorticoid exposure are more pronounced in SO pregnancy. We also considered whether there were sex-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 49 publications
(69 reference statements)
4
64
0
2
Order By: Relevance
“…Similarly, Vangeel et al ( N  = 45) found an interaction such that prenatal anxiety was positively associated with cord blood DNA methylation in the GABA-B receptor subunit 1 gene ( GABBR1 ) in infant boys but not girls [53]. Mina et al found sex-specific associations suggesting that infant girls might be particularly susceptible to the effects of prenatal maternal distress on placental mRNA levels of genes regulating fetal glucocorticoid exposure and placental growth [68]. Finally, data from the Barwon Infant Study ( N = 481) showed no evidence of sex dependence in associations between PNMS and cord blood NR3C1 glucocorticoid receptor gene methylation [25].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Vangeel et al ( N  = 45) found an interaction such that prenatal anxiety was positively associated with cord blood DNA methylation in the GABA-B receptor subunit 1 gene ( GABBR1 ) in infant boys but not girls [53]. Mina et al found sex-specific associations suggesting that infant girls might be particularly susceptible to the effects of prenatal maternal distress on placental mRNA levels of genes regulating fetal glucocorticoid exposure and placental growth [68]. Finally, data from the Barwon Infant Study ( N = 481) showed no evidence of sex dependence in associations between PNMS and cord blood NR3C1 glucocorticoid receptor gene methylation [25].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown sexual dimorphism of gene expression in the human placenta [4042] and in response to adverse environments e.g. maternal distress [43]. In murine models obesity alters placental morphology, cell proliferation and inflammation [44] and maternal diet alters placental gene expression [45] and epigenetic systems [46] in a sexually dimorphic manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, while a low protein diet decreased 11β-HSD2 activity near the end of pregnancy, it had the opposite effect earlier in pregnancy [17]. Similarly, maternal stress generally reduces placental 11β-HSD2 activity [5,18,19], although some studies have found the opposite pattern [5]. The effects of maternal overnutrition and/or obesity on placental 11β-HSD2 activity have received less study [20], although a high-fat diet decreases placental 11β-HSD2 expression and enzymatic activity in mice [21,22].…”
Section: Introductionmentioning
confidence: 99%